Quantum-based first-principles study of gas molecules (O\(_{2}\), CO\(_{2}\), NO\(_{2}\)) interaction on monolayer germanene - HERMANTO, Arief; PRAYOGI, Harmon; NUGRAHENI, Ari Dwi; PARTINI, Juliasih; SHOLIHUN, Sholihun (Journal of Metals, Materials and Minerals, 2023)
We perform calculations of the adsorption energy of O2, CO2, and NO2 molecules on germanene by using the density functional theory (DFT). We find two favorable configurations for O2, the U-site and V-site configurations with similar adsorption energies of -4.10 and -4.32 eV. As for NO2, we find two favorable configurations, the T-site and DB-site configurations. The T-site configuration is 0.98 eV more stable than the IB-site one, and both configurations are chemically adsorbed by germanene. On the contrary for CO2, we find a T-site configuration with adsorption energy of 0.42 eV and the configuration physically adsorbed by germanene.